COVID-19: Macroeconomic dimensions in the developing world - Tony Addison; Kunal Sen; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The COVID-19 pandemic represents an unprecedented global crisis. The task for economic policy is to help keep people alive, enterprises afloat, and households out of poverty. The pandemic has macroeconomic dimensions. First, it affects macroeconomic stability and growth. Second, the tools of macroeconomic policy-fiscal and monetary policy together with debt management and exchange rate policy-must deal with the economic shock. Simultaneously, policy makers must find fiscal space to fund health, social protection, and livelihood support. Third, success in dealing with the virus itself will be a big determinant of macroeconomic outcomes: the size of the GDP loss, the duration of the recession, and the outcomes for the fiscal deficit and debt ratios. This paper discusses these macroeconomic dimensions, focusing on the developing world. The paper concludes that the pandemic could reinforce the existing trend towards higher social inequality.
Keywords: E71; F01; I15; O11; 330; commodities; COVID-19; debt; growth; inequality; macroeconomic policy; poverty